PERCEPTION OF KNOWLEDGE AND ATTITUDES TOWARDS COVID-19 IN A GROUP OF CITIZENS FROM THE URBAN AREA OF HUÁNUCO - Ruiz-Aquino, Mely (2022)
The COVID-19 pandemic has caused a crisis in health systems around the world with a rapid increase in human contagion. As well, a gap is identified in the knowledge of COVID-19 prevention in the community context. Objective: To determine the relationship between the perception of knowledge and the type of attitudes towards COVID-19 among citizens in the urban area of Huánuco, Peru. Methods: An analytical and cross-sectional study using a quantitative approach was conducted in the city of Huánuco between March and May 2020. The sample consisted of 168 people. A perception of knowledge questionnaire and a previously validated COVID-19 attitude scale have been applied. The chi-square test was applied, a p-value less than 0.05 has been taken into account. Results: When analyzing the perception of knowledge about COVID-19, 62.5% (105) said “they feel they do not know”. The analysis of the type of attitudes viewed by citizens towards COVID-19 revealed that 63.1% (106) of respondents had negative attitudes. Statistically significant association was found between the perception of knowledge and the type of attitudes towards COVID-19 (p<0.005). Conclusions: There is a relationship between the perception of knowledge and the type of attitudes toward COVID-19 among a group of citizens from the Huanuco urban area.